Patterns of Software Development Process - Bolaños Castro, Sandro Javier; González-Crespo, Rubén; Medina García, Víctor Hugo (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
This article presents a set of patterns that can be found to perform best practices in software processes that are directly related to the problem of implementing the activities of the process, the roles involved, the knowledge generated and the inputs and outputs belonging to the process. In this work, a definition of the architecture is encouraged by using different recurrent configurations that strengthen the process and yield efficient results for the development of a software project. The patterns presented constitute a catalog, which serves as a vocabulary for communication among project participants [1], [2], and also can be implemented through software tools, thus facilitating patterns implementation [3]. Additionally, a tool that can be obtained under GPL (General Public license) is provided for this purpose.
Keywords: software process; patterns; IJIMAI